Cultural anthropology : - Bodley, John H. (Mayfield Pub. Co., 1994)
An introductory cultural anthropology text, this book introduces basic concepts of cultural anthropology by comparing cultures of increasing scale and focusing on specific universal issues. "Understanding how tribes, states, and global systems work and how they differ might help citizens design a more secure and equitable world," says Bodley; it is this advocacy position that informs the text.